Development of Green Hydrogen Economy and its Feasibility in Electricity Generation in Europe - Mäkelä, Mikael Erkki Matias (My University, 2021)
One prospective solution to manage the instability of renewable energy sources and reduce emissions in the energy sector is to produce and utilise clean and low-carbon hydrogen. The European Union has announced its target to make hydrogen a main decarbonisation option. This study examines the utilisation of green hydrogen in electricity generation, identifies its challenges and significant benefits. The aim was to provide comprehensive information and estimate the green hydrogen economy and future developments. This thesis was executed as an assignment for Wärtsilä's Growth & Development department. The exponentially increased objectives in the green hydrogen economy have raised the concern of whether each sector has a sufficient capacity to utilise hydrogen and what happens if green hydrogen cannot be produced as affordable as aimed. These questions point out the need for research about the potential of green hydrogen in electricity generation. The thesis focused on reviewing and analysing the European hydrogen economy presented in the literature and commercial sources. The aim was to discover a common line between the various perspectives and assess the direction where the European hydrogen economy is most preferably heading in the long term. In this thesis, the different scenarios for using green hydrogen in electricity generation were implemented, based on which each variable's impact was assessed. Also, the competitiveness of green hydrogen under different circumstances was evaluated. The results showed that green hydrogen has a great potential to become significant long-term energy storage and fuel for electricity generation. Still, it will require development in line with ambitious targets. The use of hydrogen in electricity generation is limited by technical and economic challenges. At current production prices, green hydrogen is not an attractive option to the electricity generation needs. The trend is that sectors such as industry, which currently has the highest hydrogen consumption, also will be the most significant users of green hydrogen, at least in the initial phase.

Yhtenä vaihtoehtona uusiutuvan energian vaihtelevan tuotannon tasapainottamiseksi ja energiasektorin päästöjen vähentämiseksi on tuottaa ja hyödyntää puhdasta, vähäpäästöistä vetyä energiasektorilla. Euroopan Unioni on julkaissut tavoitteensa kyseisten vetyvaihtoehtojen laajasta hyödyntämisestä tulevaisuudessa. Tässä tutkimuksessa tarkasteltiin vedyn hyödyntämistä sähköntuotannossa, sen haasteita ja merkittävimpiä etuja. Työn tavoite oli tarjota tietoa ja arvioita uusiutuvan vedyn markkinoista ja tulevaisuuden kehityksestä Euroopassa. Työ toteutettiin Wärtsilän energialiiketoiminnan Euroopan Growth & Development osastolle. Vetytalouden kunnianhimoinen kasvutavoite synnyttää huolen, onko vedyn menestymiselle edellytykset sähköntuotannossa. Millaisia vaikutuksia havaitaan, jos vetyä ei pystytä tuottamaan yhtä edullisesti kuin on tavoiteltu? Tällaiset kysymykset osoittivat tarpeen tutkia, millaiset hyödyntämismahdollisuudet uusiutuvalla vedyllä on sähköntuotannossa. Työssä keskityttiin kirjallisuudessa sekä kaupallisissa lähteissä esitettyjen tulosten ja arvioiden tarkasteluun ja analysointiin. Tarkoituksena oli analysoida, mihin suuntaan Euroopan vetymarkkinat ovat kehittymässä tulevaisuudessa. Tässä työssä rakennettiin myös skenaariotutkimus, jonka perusteella analysoitiin eri muuttujien kehityksen vaikutusta vedyn kustannuksiin ja sitä kautta sen kilpailukykyyn. Tulokset osoittivat, että vihreällä vedyllä on suuri potentiaali tulla osaksi sähköntuotantoa tulevina vuosikymmeninä, mutta se vaatii kunnianhimoisten tavoitteiden mukaista kehitystä. Vedyn hyödyntämistä sähköntuotannossa rajoittavat sekä teknilliset että taloudelliset haasteet. Uusiutuva vety ei ole nykyisillä tuotantohinnoilla houkutteleva vaihtoehto sähköntuotannon tarpeisiin. On nähtävissä trendi, että sektorit kuten teollisuus, jossa tällä hetkellä vedyn kulutus on suurinta, tulevat olemaan merkittävimpiä uusiutuvan vedyn hyödyntäjiä lähivuosina.
Keywords: fi=Energiatekniikka|en=Energy Technology|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|